2018
DOI: 10.2147/ott.s162934
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine tumor of the common bile duct: a case report and review of the literature

Abstract: We report a rare case of neuroendocrine tumor (NET) in the common bile duct (CBD). The patient is a 56-year-old female who presented to our department with symptoms of fever but without jaundice. A preoperative examination showed a tumor in the CBD. The tumor volume was almost 5.5 × 4.5 × 4 cm3, which is the biggest NET in the CBD reported on PubMed. The imaging results (computed tomography [CT] and magnetic resonance imaging [MRI]) were not consistent with CBD adenocarcinoma. The tumor appeared to oppress the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 17 publications
0
19
0
3
Order By: Relevance
“…21 Since Pilz reported the first case of biliary NET in 1961, a review of the literature revealed only 92 previously reported cases. [2][3][4] The reason for the rarity of NET in the biliary tree is explained by the fact that chromaffin and Kulchitsky cells, which are the origin of NET, are rarely present in the biliary tree. 22 In the digestive system, the 2010 WHO classified neuroendocrine neoplasms as G1, G2, or G3 according to the proliferative activity measured by counting mitosis or evaluating the Ki-67 LI.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…21 Since Pilz reported the first case of biliary NET in 1961, a review of the literature revealed only 92 previously reported cases. [2][3][4] The reason for the rarity of NET in the biliary tree is explained by the fact that chromaffin and Kulchitsky cells, which are the origin of NET, are rarely present in the biliary tree. 22 In the digestive system, the 2010 WHO classified neuroendocrine neoplasms as G1, G2, or G3 according to the proliferative activity measured by counting mitosis or evaluating the Ki-67 LI.…”
Section: Discussionmentioning
confidence: 99%
“…In a review by Michalopoulos et al, preoperative diagnosis was reported to be feasible in only four of 78 cases based on elevated serum serotonin levels (two cases) and biopsy during endoscopic retrograde cholangiopancreatography (ERCP) (two cases). To the best of our knowledge, no previously reported biliary NET cases have described preoperative brush cytology . Herein, we report on brush cytology of NET in the common hepatic duct (CHD).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations